2010
DOI: 10.1212/wnl.0b013e3181e2414b
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic damage is far more severe than demyelination in NMO

Abstract: Astrocytic damage reflected by elevated CSF glial fibrillary acidic protein is a clinically relevant, primary pathologic process in neuromyelitis optica, and is far more severe than demyelination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
162
6
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(182 citation statements)
references
References 36 publications
5
162
6
9
Order By: Relevance
“…31 In neuromyelitis optica, astrocytes die before demyelination occurs, and cerebral spinal fluid or serum levels of S100B correlate with the clinical manifestations of the disease. 32 We explored the possibility that astrocyte death in ODS induces S100B release by evaluating serum S100B levels after hyponatremia correction. We observed that there was a significant increase in serum S100B at 12 hours postcorrection that continued until 3 days postcorrection (P Ͻ 0.001 compared with S100B levels before the correction; Figure 6A).…”
Section: Early Downregulation Of Astrocyte-oligodendrocyte Gap Junctimentioning
confidence: 99%
“…31 In neuromyelitis optica, astrocytes die before demyelination occurs, and cerebral spinal fluid or serum levels of S100B correlate with the clinical manifestations of the disease. 32 We explored the possibility that astrocyte death in ODS induces S100B release by evaluating serum S100B levels after hyponatremia correction. We observed that there was a significant increase in serum S100B at 12 hours postcorrection that continued until 3 days postcorrection (P Ͻ 0.001 compared with S100B levels before the correction; Figure 6A).…”
Section: Early Downregulation Of Astrocyte-oligodendrocyte Gap Junctimentioning
confidence: 99%
“…27 Neuropathologic and CSF analyses in NMO demonstrated massive destruction of astrocytes in acute NMO lesions, but there were no such changes in MS. 28,29 More recent experimental studies clearly showed that AQP4 antibody derived from patients with NMO, predominantly of the IgG1 subclass, ac- tivated the complement pathway efficiently and caused astrocytic necrosis in cell culture and NMOlike lesions in animals with experimental autoimmune encephalomyelitis. 30 Purified IgG from AQP4 antibody-negative patients did not induce those morphologic changes.…”
Section: Clinical Features Of Aqp4 Antibody-negative Cmsmentioning
confidence: 99%
“…However, unique clinical and laboratory features found in NMO patients like poor functional recovery and rare chronic progression, relatively common involvement of optic chiasm, spinal cord lesions longitudinally extending over three or more vertebral segments, absence of oligoclonal immunoglobulin G (IgG) bands, and prominent elevation of glial fibrillary acidic protein (GFAP) levels in the cerebrospinal fluids differentiate NMO patients from other demyelinating diseases. Additionally, pathological findings in NMO patients like perivascular deposition of immunoglobulins and complement, severe astrocytic damage (demonstrated by loss of AQP-4 and GFAP stainings) and a relative preservation of myelin strongly suggest that NMO is a clinical entity distinct from MS 5,6 .…”
Section: Introductionmentioning
confidence: 99%